KEMAHIRAN MENYIMAK DALAM PROSES PEMBELAJARAN BAHASA ARAB - Jabir, Muhammad (State Institute of Islamic Studies (IAIN) Palu, 2010)
According to linguists, there are four skills of language which must be mastered by leaners learners in learning a language, Arabic is no exception. First listening skill, second speaking skill, third reading skill and fourth writing skill. In this article, the author will focus his discussion on the first skill, namely listening skill. The reason is that without good listening skill, there will be a lot of misunderstanding in communication among the language users.Kata Kunci: Kemahiran, Menyimak, Pembelajaran, Bahasa Arab